Resistance of Escherichia coli Isolated from Water Sources on West Lombok Farms to Antibiotics - Ningtyas, Novarina Sulsia Ista'In; Alfiana Laili Dwi Agustin; Bq. Malikah Hr; Baiq Susdiana Fibrianti (Universitas Airlangga, 2024)
Antibiotics are frequently used arbitrarily in livestock industry without regards for dosage or norms use. The administration of antibiotics to livestock can lead to a decline in their efficacy and contribute to the emergence of antibiotic resistance, hence posing challenges to the quality and safety of livestock products. Escherichia coli (E.coli) is recognized as a bacterial indicator pollution. This study aims to determine the resistance of E. coli to the antibiotic's penicillin G and tetracycline. The study used a survey method with cross-sectional study design in July, 2023 on farms located in West Lombok. Testing was carried out on 10 water samples taken from water sources on farms that showed 2 negative samples and 8 positive samples of E. coli on EMBA media, then continued with resistance tests using Penicillin G and Tetracycline antibiotics by measuring the inhibitory zone that formed. The results of this study showed that E.coli samples experienced resistance to Penicillin G as many as 8 samples and tetracycline as many as 6 samples. E.coli bacteria isolated from drinking water have experienced resistance to antibiotics Penicillin G by 100% and Tetracycline 75%.